Associations between students' bystander behavior and individual and classroom collective moral disengagement. Issue 3 (16th March 2021) - Sjögren, Björn; Thornberg, Robert; Wänström, Linda; Gini, Gianluca
Abstract: This study examined whether students' bystander behaviours in peer victimisation were associated with individual (IMD) and classroom collective moral disengagement (CMD). Self-report survey data were analysed from 1577 Swedish students in fifth grade. Multilevel analyses revealed that, when witnessing peer victimisation, students more often sided with the victimisers if they belonged to classrooms high in CMD, especially if they simultaneously were high in IMD. Furthermore, staying passive was associated with higher levels of IMD and CMD, whereas defending the victims was associated with lower levels of IMD and CMD. Taken together, our findings suggest that moral disengagement beliefs both at the individual and at the classroom-level contribute to explain variability in students' bystander behaviours, which has potential implications for prevention and intervention work.